The 2015 European Refugee Crisis and Residential Housing Rents in Germany - Kathleen Kürschner Rauck; Michael Kvasnicka (Institute of Labor Economics (IZA), 2018)
We study the impact of the 2015 mass arrival of refugees to Germany on residential housing rents. Using unique data on end of year county-level refugee populations and data on monthly offers of flats for rent from Germanyâ exteuro™s leading online property broker Immobilienscout24, we find strong evidence in difference-in-differences regressions for a negative effect of refugee immigration on rental prices. Adverse price effects, however, appear attenuated in the heyday of the crisis in late 2015 if a larger share of refugees is housed in decentralized accommodation. Various robustness checks corroborate our findings, including IV regressions that exploit for identification information on the pre-crisis location of refugee reception centers and group quarters.
Keywords: F22; R23; R21; R31; 330; housing rents; refugee migration; Germany